Hepatic and pancreatic involvement in hereditary hemorrhagic telangiectasia: quantitative and qualitative evaluation with 64-section CT in asymptomatic adult patients - Barral, Matthias; Sirol, Marc; Placé, Vinciane; Hamzi, Lounis; Borsik, Michel; Gayat, Etienne; Boudiaf, Mourad; Soyer, Philippe (European radiology, 2012)
Purpose To analyse quantitatively and qualitatively asymptomatic hepatic and pancreatic involvement in hereditary haemorrhagic telangiectasia (HHT) using 64-section helical CT. Materials and methods The 64-section helical CT examinations of 19 patients with HHT (8 men, 11 women; mean age, 58.6 years) were quantitatively and qualitatively analysed and compared to those of 19 control subjects who were matched for age and sex. Comparisons were made using univariate analysis. Results Dilated and tortuous intrahepatic arterial branches was the most discriminating independent variable ( P < 0.0001) and had the highest specificity (100%; 19/19; 95%CI: 82%–100%) and accuracy (97%; 37/38; 95%CI: 86%–100%) for the diagnosis of HHT. Heterogeneous enhancement of hepatic parenchyma, intrahepatic telangiectases, hepatic artery to hepatic vein shunting, hepatic artery enlargement (i.e. diameter > 6.5 mm) and portal vein enlargement (i.e. diameter > 13 mm) were other variables that strongly correlated with the presence of HHT. Intrapancreatic telangiectases and arteriovenous malformations were found in 42% and 16% of patients with HHT, respectively. Conclusion Liver and pancreatic involvement in asymptomatic HHT patients is associated with myriad suggestive findings on 64-section helical CT. It can be anticipated that familiarity with these findings would result in more confident diagnosis of HHT. Key Points • HHT hepatic and pancreatic involvement is associated with myriad findings shown by CT . • 64-section helical CT depicts hepatic and pancreatic involvement in asymptomatic HHT patients • Multidetector CT shows discriminating intrahepatic abnormalities for the diagnosis of HHT • CT heightens confidence in diagnosing hereditary haemorrhagic telangiectasia in equivocal cases